THE NEED FOR CULTURAL CHANGE: A CASE STUDY DISCUSSION - Karen Cacciattolo (European Scientific Journal, ESJ, 2014)
This paper discusses the significance of the organisational culture and the research carried out within the University of Malta to test whether a cultural change is required in the organisation. The research examined the views and comments of the stakeholders of the organisation on the present organisational culture namely, students, administrative staff and academic staff from various departments. A twofold research methodology was chosen. Initially, a quantitative stage involving questionnaires was sent to all participants. This was followed by a qualitative stage involving twelve participants taking part in the in-depth structured interviews. Secondary data was also used for the study, which guided the researcher in understanding better the present organisational culture.